Analysis of Factors Related to BPJS Patient Satisfaction at Kabawo Community Health Center, Muna Regency, Southeast Sulawesi Province - Marliana, Marliana; Pajung, Christian Bertom; Toar, Jilly; Mamuaja, Prycilia Pingkan; Langitan, Fentje; Lolowang, Djajty M. (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Health is a fundamental human right as mandated by the 1945 Constitution and Law Number 17 of 2023, which affirms that the state is responsible for providing proper healthcare services. To achieve this, the government established BPJS Health as the implementing body of the National Health Insurance (JKN) system, aiming to ensure equitable and high-quality healthcare services for all Indonesian citizens. The success of a health insurance program is not only assessed by service accessibility but also by the level of patient satisfaction with the quality of care received. This study aims to identify the factors associated with the satisfaction of BPJS patients at Kabawo Community Health Center, Muna Regency, Southeast Sulawesi Province. The research employed a quantitative analytic design with a cross-sectional approach. The study population included all BPJS participants visiting the Kabawo Health Center, with a sample of 100 respondents selected using simple random sampling. The results showed a significant relationship between age (p = 0.031), sex (p = 0.043), occupation (p = 0.018), membership status (p = 0.003), and membership duration (p = 0.000) with BPJS patient satisfaction. Meanwhile, education (p = 0.156) was not significantly associated with patient satisfaction. These findings indicate that certain characteristics may influence patients’ perceptions of service quality at primary healthcare facilities.